Underutilized vegetables for health and prosperity - Prajapati, Uma; Asrey, Ram; Meena, Nirmal Kumar (Indian Horticulture, 2019)
Underutilized vegetables are rich and good source of vitamin, minerals and secondary metabolites which help in reducing various health problems and protect from diseases. Leafy vegetables like amaranths, chenopodium, water spinach, basella are known for their bioactive and basic nutrient compounds such as folic acid, vitamin A and C, riboflavin, crude fibre, minerals like Ca, P and Fe. Besides leafy vegetables, jack bean, winged bean, chow-chow, Kakrol, Kachri and Kundru are important vegetables known for their richness in protein and secondary metabolites which enhance their nutraceutical value. These minor vegetables play a crucial role to overcome malnutrition and to cure many health related problems in tribal and rural areas. These are not commercially cultivated but still are used in some parts of India to meet nutritional requirements as well as raise farmers’ income.